Comparative Analysis of Blood and Marrow Cellular Structure of White Mice Infected With Bacillus Anthracis Different Genotypes - V. I. Dubrovina; T. P. Starovoitova; E. V. Kravets; T. A. Ivanova; Z. F. Dugarzhapova; O. V. Gavrilova; O. V. Yur’eva; T. T. Shkaruba; S. V. Balakhonov (Acta Biomedica Scientifica, 2020)
Background. Detection of the pathogenicity factors is one of the actual directions in studying of the anthrax causative agent. First of all, it includes the presence of tripartite toxin, capsule and the related structural and regulatory genes. Their presence or absence is defined by structural changes in cellular structure of blood and immunocomplex organs of a macroorganism.Objective: To conduct a comparative analysis of subpopulational structure of marrow and peripheral blood cells at anthrax infection in experimental animals and to trace dynamics of the infectious process caused by Bacillus anthracis of different genotypes.Methods. Comparative examination of subpopulational structure of red marrow and peripheral blood cells of white mice in dynamics of the infectious process caused by B. anthracis of different genotypes was conducted. Also, neutrophil maturing index and leucoerythrocytic correlation were calculated in red marrow. Degree of manifestation of neutrophil pathological granularity was revealed in peripheral blood smears stained by the Freifeld’s method. Statistical processing of the received data was conducted using the computer program “Statistics”, version 6 (Novosibirsk). Authentic results were considered if the error probability was less than 0.05 (р < 0.05) in relation to the control.Results. It is revealed that alterations in white mice infected by B. anthracis strains with the same set of plasmids are significantly various.Conclusion. The resulted data permit to assume that the distinction of pathological alterations in peripheral blood and red marrow is probably connected with the other factors of the pathogen invasiveness like enzymatic activity, ability to adhesion and many others.